(Don't) Mind the effort: Effects of contextual interference on ERP indicators of motor preparation. (6th July 2016) - Frömer, Romy; Stürmer, Birgit; Sommer, Werner
Abstract: Motor learning is associated with a decrease in frontal control‐related brain activity and increase of central and parietal motor‐related activity. Contextual interference (CI), manipulated typically by blocked versus randomized training schedules, affects motor learning, resulting in inferior performance during training but in superior performance during retention and transfer. The CI effect is often explained by increased processing demands under high CI training. Consistently, in the motor preparation phase, the activity of control‐ and attention‐related brain areas is increased under high CI. Here, we investigated the effect of CI on learning‐related changes in ERPs during motor preparation. Participants learned throwing at virtual targets and were tested for retention in the target condition 1 week later. The frontal P3 component decreased with learning during the first session and across sessions. In addition, there was a trend for a stronger reduction of P3 during retention after high CI training. Both initial and late contingent negative variation (iCNV and lCNV) amplitudes decreased with learning and showed a significantly stronger reduction under high CI. We conclude that CI modulates the interplay of cognitive and motor processes in the preparatory phase of motor learning and that a stronger involvement of cognitive processes during high CI training accounts for differential effects of CI on ERP indicators of motor preparation during retention.